Typical pain experience but underestimation of others' pain: Emotion perception in self and others in autism spectrum disorder. (August 2018) - Thaler, Hanna; Skewes, Joshua C; Gebauer, Line; Christensen, Peer; Prkachin, Kenneth M; Jegindø Elmholdt, Else-Marie
Difficulties in emotion perception are commonly observed in autism spectrum disorder. However, it is unclear whether these difficulties can be attributed to a general problem of relating to emotional states, or whether they specifically concern the perception of others' expressions. This study addressed this question in the context of pain, a sensory and emotional state with strong social relevance. We investigated pain evaluation in self and others in 16 male individuals with autism spectrum disorder and 16 age- and gender-matched individuals without autism spectrum disorder. Both groups had at least average intelligence and comparable levels of alexithymia and pain catastrophizing. We assessed pain reactivity by administering suprathreshold electrical pain stimulation at four intensity levels. Pain evaluation in others was investigated using dynamic facial expressions of shoulder patients experiencing pain at the same four intensity levels. Participants with autism spectrum disorder evaluated their own pain as being more intense than the pain of others, showing an underestimation bias for others' pain at all intensity levels. Conversely, in the control group, self- and other evaluations of pain intensity were comparable and positively associated. Results indicate that emotion perception difficulties in autism spectrum disorder concern the evaluation of others' emotional expressions, with no evidence for atypical experience of own emotional states.